The Role of Higher Education Policies in Science Production (Case Study; Graduate Degrees in University) - Qasemi, Hamid Reza; Behzadi, Milad (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The present study aimed to investigate the role of higher education policies in science production in postgraduate education. This study was considered causal research in terms of the method used. In the present study, the statistical population of this study includes graduate students of Arak University. Morgan's Table was used for sampling, and the convenience sampling method (also known as availability sampling) was used. The sample size was 323 people. According to the results, higher education policies can positively and significantly affect science production through structuring higher education, subsidy allocation to graduate education, investment in higher education, building culture for higher education, the applicability of higher education, innovation support).